Earnings pressure and R&D cut: the moderating effects of family control and debt. Issue 4 (26th October 2020) - Le, Quang-Anh; Lee, Cheng-Yu
Abstract : Purpose: This study aims to analyze the link between earnings pressure and R&D cut as well as the moderating effects of family control and debt. Design/methodology/approach: In total, 6, 130 firm-year observations of Taiwanese-listed firms were used to test the hypotheses by using a panel data regression with fixed effects estimation. Findings: The study reveals that earnings pressure is positively related to R&D cut, and this relationship can be softened when having the presence of family control and debt. Research limitations/implications: This study is conducted based on some conditions: data collection comes from a single source, earnings pressure mainly comes from analysts, R&D intensity is significant among industries, debt is a given condition to managers. Future studies, thus, are suggested to use other approaches to have further information and extend the knowledge without these conditions. Practical implications: Under the pressure of meeting analyst forecast, managers have more opportunities to flourish their priority on improving temporary profits rather than implementing R&D investments with costly budget but unpredictable outcomes. In addition to responding to the positive effect of earnings pressure on trimming long-term corporate investments, this study also found some corporate governance mechanisms to soften the managerial short-termism behavior. Originality/value: The findings partially contribute to broadening the existing knowledge base on the impact of earnings pressure on corporate activities and how some mechanisms serve as moderators.